Narrow-field supracricoid partial laryngectomy: Procedure development and initial clinical experiences. Issue 3 (June 2023) - Nakayama, Meijin; Wada, Takashi; Isono, Yasuhiro; Sano, Daisuke; Nishimura, Goshi; Oridate, Nobuhiko; Holsinger, F. Christopher; Orosco, Ryan
Abstract: Objectives: To evaluate the feasibility of narrow-field supracricoid partial laryngectomy with cricohyoidoepiglottopexy (NF-SCPL-CHEP). Methods: Between 2019 and 2020, five patients with glottic cancers underwent NF-SCPL-CHEP. The mean durations of surgical drains, tracheostomy canula, and nasogastric tube use were evaluated. Length of stay following NF-SCPL-CHEP was compared with that of our open SCPL historical controls. A case summary is provided for the first patients, with detailed information about postoperative management and function. Results: All five patients achieved uneventful postoperative recoveries without major complications. The average time for surgical drains, tracheostomy canula, and nasogastric tube use were 2, 15, and 46 days, respectively. The mean overall hospitalization period was 36 days for NF-SCPL-CHEP patients. The mean period of hospitalization based on our early experiences between 1997 and 2005 with classical open SCPL was 72 days. All patients were fully functional and local recurrences or distant metastases were not encountered during a mean observation period of 39 months. Conclusions: NF-SCPL-CHEP with 6 cm cervical access appeared technically feasible and oncologically sound in this initial clinical experience. An extra 2 cm incision, which enabled lateral neck dissection, was not felt to detract from the overall minimally invasive basis of NF-SCPL-CHEP. The clinical results were encouraging with limited complications and predictable postoperative recovery. The length of stay for patients undergoing NF-SCPL was half that of open SCPL historical controls. Less damages to local circulation may associate with the positive influences. Further study with a large patient sample across multiple institutions are needed to carefully evaluate long-term functional and oncological outcomes.